History in the making [videorecording].
A video on the Feb. 7, 1986 snap presidential election which culminated in the downfall and exile of Ferdinand E. Marcos and the succession of Corazon C. Aquino on February 25, 1986, following a violent revolt supported by hundreds of thousands civilians.